TECHNOLOGY OF USING THE PUBLIC-PRIVATE PARTNERSHIP MODEL IN VOCATIONAL EDUCATION (Innovative professional education, 2023)
The introduction of public-private partnership into the professional education system is due to a number of factors. In particular, seven factors have been identified. An appropriate model is being created for the implementation of public-private partnership inprofessional education. For its implementation in the practice of professional (vocational and technical) education institutions, a technology is being developed that guarantees obtaining the planned result.
Keywords: public-private partnerships, vocational education, institutions of professional (vocational and technical) education, technology